A New Paradigm of Literacy: A Book Review of Literacy and Education - Akhmad Idris (Pusbindiklatren Bappenas, 2022)
The industrial revolution is a term to label industrial development from era to era. The first phase started in the early 18th century and has now entered the fourth phase, or 4.0. Davies (2015) stated that the 1.0 industrial revolution began with the use of steam engines and machines to replace human force. In the 2.0 industrial revolution, steam engines were replaced by electrical production machines as mass production engines. The 3.0 industrial phase was characterized by the emergence of computers in the 1970s. Finally, the rapid development of interconnected technology, sensor, and data analysis became the signs of the 4.0 industrial revolution emergence. The development has impacted conventional industries in the form of digitalization. Online transportation mode is one of the most prominent impacts of the fourth industrial revolution. This phase also creates massive shifts in many sectors, such as the use of video calls, fingerprints, and face scanners as security locks, social media to connect people from all around the world, and the digitalization of books, magazines, and journals